Exploratory spectroscopic and computational studies of the anion binding properties of methyl hyocholate in organic solvent. Issue 13 (30th March 2017) - Fantin, Giancarlo; Fogagnolo, Marco; Delso, Ignacio; Merino, Pedro
Abstract: The binding properties of methyl hyocholate1a toward F −, Cl −, Br − and CH3 CO2 − anions were explored by 1 H and 13 C NMR, ESI-MS measurements and computational calculations. The 1 H NMR titration suggested that1a forms a 1:1 complex with the selected anions. These complexes have also been detected by ESI-MS measurement even though the MS spectra showed that the stoichiometry of the predominant host-guest species in the gas phase is 2:1. 13 C NMR and computational data suggested that the hydroxyl groups at C6 and C7 positions are more involved than the hydroxyl group at C3 position in the binding of spherical F −, Cl −, Br − anions while in the case of the Y-shaped acetate ion two different conformers (in equilibrium) are present: the first showing interaction with both the two hydroxyl groups at C6 and C7 positions, the second also involving the participation of the third hydroxyl group at C3 position. Graphical abstract: